Evaluation of Green Performance Appraisal Implementation on Innovation and Energy Efficiency at PT Integra Solusi Utama - Huraerah, Alkadry; Rahma Yusuf, Qamaria; Andilonge, Marwin; Gifari Sono, Moh (Journal of Management, 2025)
This study aims to analyze the effect of Innovation, GPA Implementation, and Managerial Support on Energy Efficiency in an organization. This study uses a quantitative approach with multiple linear regression methods. Data was obtained through a survey involving respondents from various industrial sectors. Statistical tests used include R Square, F test (ANOVA), and t test to test the relationship between independent and dependent variables. The results show that the regression model used is significant (p = 0.000), with an R Square value of 53.6%, which means that the variables Innovation, GPA Implementation, and Managerial Support can explain 53.6% of the variation in Energy Efficiency. The t-test showed that only GPA Implementation had a significant effect on Energy Efficiency (p = 0.025), while the Managerial Support and Innovation variables showed no significant effect. This finding confirms that GPA Implementation is the main contributing factor in improving Energy Efficiency, so organizations need to focus more on effective GPA implementation strategies. This research also suggests that further studies consider other factors that can influence energy efficiency, such as sustainability policies and energy-saving technologies.